Desenvolvimento profissional de professores: o que pensam professores e professoras de Educação Infantil - Aveledo, Edilene Aparecida Barros da Silva (2023)
This research focused on teachers’ professional development. We abide by the concept that professional development must represent transformation in such way that it transcends training, i.e., that it represents the acquisition of professional knowledge, including aspects such as work conditions and the Improvement of workers’ conditions – payment, career paths, hiring and institutional conditions – among others. The research took place at an Early Childhood Education school in the city of Itanhaém, located in the coastal line of São Paulo, with eight participant teachers. General objective was to identify what is the concept of professional development of Early Childhood Education teachers and how they understand their own professional development paths. Specific objectives were: a) to identify Indicators of teachers’ professional development; and b) to analyse what teachers believe to be necessary for their professional development. Conversation Circles were used as methodological procedure, under the premise that dialog as a single moment of sharing, given that Conversation Circles presume the exercise of talking and listening. Results pointed to the demand for the implementation of public policies for professional appreciation